The Problems in Learning English at SMP Negeri 26 Makassar - Jumratun, Jumratun; Tahir, Muh.; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aimed to assess the students’ problems in learning English and factors that cause the students’ problems in learning English at SMP Negeri 26 Makassar. There were 6 students in the eighth grades who participated in this research. This is qualitative descriptive research which used observation and interview as the data collections technique. Based on findings, the data showed that there were eight problems faced by students in learning English they are: 1) Lack of vocabulary, 2) Vocabulary problem, 3) Lack of grammar mastery, 4) Anxiety, and 5) Unsupportive environment, 6) Spelling problem, 7) Listening difficulties, 8) Missintonation and there were three factors led to students’ problems in learning English, namely motivation, personality, and environment.